Curah Hujan Terhadap Produktivitas Padi Dan Ubi Kayu: Analisis Statistik Di Kabupaten Serdang Bedagai - Arinda, Dela; Afifi, Annida Fauziyyatul; S, Safrizal; Marsudi, Sundari (Jurnal Sains Agro, 2025)
Rainfall is one of the climatic factors that influences the productivity of food crops. This study aims to analyze the relationship between rainfall and the productivity of rice and cassava in Serdang Bedagai Regency. The data used are annual secondary data for the period 2013–2024, consisting of rainfall records and the productivity of rice and cassava commodities. The relationship was analyzed using Pearson correlation and simple linear regression methods. The results show that rainfall has a positive and significant relationship with rice productivity, with a correlation coefficient of 0.70 and an R² value of 0.489, indicating that nearly 49% of the variation in rice productivity can be explained by rainfall. Meanwhile, the relationship between rainfall and cassava productivity is positive but not statistically significant (r = 0.60; R² = 0.37; p 0.05), indicating a weaker influence. The effect of rainfall is more evident on rice productivity compared to cassava. These findings highlight the need for improved water management and climate adaptation strategies, particularly in the rice farming systems of Serdang Bedagai Regency.